Parental Involvement In Their Children’s English As A Second Language (Esl) Learning In Primary Schools In Malaysia - Alias, Nurul Zulaikha (2024)
This study examines parental involvement in their children’s ESL learning in Malaysian primary schools, specifically focusing on the B40 (bottom 40%) and T20 (top 20%) socioeconomic groups. Employing qualitative interviews with 12 participants, the research explores the diverse roles, perspectives, and perceived effectiveness of parental involvement in children’s ESL learning. The research objectives for this study aim to i) explore parents’ perceptions regarding their involvement in their children’s ESL learning, ii) investigate factors that influence PI in their children’s ESL learning, and iii) identify the strategies that parents use to involve themselves in their children’s ESL learning. To achieve the objectives of the study, purposive sampling are utilised. Thematic analysis is employed as the analysis method to identify patterns and insights from participant responses. The findings revealed that participants from both groups shared mutual perceptions, highlighting the importance of parental involvement in children’s ESL learning. However, their involvement varies due to several reasons, namely time constraints, knowledge in English, financial constraints, level of education. Despite these differences, both groups believed in the positive impact of their involvement. The results demonstrate that Malaysian parents actively involve themselves in their children’s ESL learning.